2011
DOI: 10.1249/mss.0b013e318207c15d
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Dosing to Retain Resistance Training Adaptations in Young and Older Adults

Abstract: We conclude that older adults require a higher dose of weekly loading than the young to maintain myofiber hypertrophy attained during a progressive RT program, yet gains in specific strength among older adults were well preserved and remained at or above levels of the untrained young.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

18
159
4
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 158 publications
(184 citation statements)
references
References 41 publications
18
159
4
3
Order By: Relevance
“…Therefore, it is advisable to decrease training volume and/or frequency during the caloric restriction period in order to maintain FFM. Bickel, Cross, & Bammman [24] conducted a study to test the efficacy of two maintenance training prescriptions on muscle mass, muscle fiber size, type distribution, and strength. To this end, the authors recruited 70 adults, who participated in a two-phase exercise trial that consisted of resistance training on 3 days/week for 16 weeks (phase 1), followed by a 32-week period (phase 2) with random assignment to detraining or one of two maintenance prescriptions (reducing the dose to one-third or one-ninth of that during phase 1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is advisable to decrease training volume and/or frequency during the caloric restriction period in order to maintain FFM. Bickel, Cross, & Bammman [24] conducted a study to test the efficacy of two maintenance training prescriptions on muscle mass, muscle fiber size, type distribution, and strength. To this end, the authors recruited 70 adults, who participated in a two-phase exercise trial that consisted of resistance training on 3 days/week for 16 weeks (phase 1), followed by a 32-week period (phase 2) with random assignment to detraining or one of two maintenance prescriptions (reducing the dose to one-third or one-ninth of that during phase 1).…”
Section: Discussionmentioning
confidence: 99%
“…16 This notion may even be more applicable to older individuals whose hypertrophic adaptations are compromised compared to young adults. 17,18 Furthermore, Degens 19 has concluded that strength and lean mass increase at a disproportionate rate in elderly people. Nevertheless, older adults are capable of increasing muscle mass and counteracting sarcopenia with resistance training, but they may require longer (>12e16 weeks) training.…”
Section: Discussionmentioning
confidence: 99%
“…This is because participation in physical activity and sport at both the recreational and competitive levels contributes to health-enhancing physiological adaptations, even among octogenarians (Bickel, Cross, & Bamman, 2011;Stessman, Hammerman-Rozenberg, Cohen, Ein-Mor, & Jacobs, 2009). From a public health perspective it is important to have more people physically active and independent because while life expectancies in most countries are increasing, disability-free years are not keeping pace (Australian Bureau of Statistics, 2002;Baker, Gupta, & Kelly, 2000).…”
Section: Introductionmentioning
confidence: 99%